"But it's just paracetamol": Caregivers' ability to administer over-the-counter painkillers to children with the information provided. Issue 3 (March 2015) - Bennin, Fiona; Rother, Hanna-Andrea
Highlights We interviewed 60 caregivers and seven pharmacists about OTC medication information. Caregivers found it difficult to understand scientific terms in all information. 10% of respondents were unable to understand dosage requirements for children. 43% of pharmacists felt the information was ineffective in preventing overdosing.